(untitled) (Archive of Conferences, 2020)
The presented article examines the effectiveness of a practical approach in teaching business Russian speech in economic universities. In recent years, in modern conditions, the contact of a teacher and a student has become an even more important element of training, and the proposed methods and techniques will contribute to a deeper and more comprehensive disclosure of the content of the educational material.